Upaya Peningkatan Hasil Belajar IPA dengan Materi Sistem Pernafasan Manusia Melalui Metode PBL Pada Siswa Kelas 8 - Azizah, Laila (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2025)
This research aims to find out whether the application of the Problem Based Learning (PBL) model can improve Science Learning Results for Class VIII UPTD SMP Negri 2 Socah. This type of research is classroom action research. The subjects of this research were 15 students in class VIII UPTD of SMP Negri 2 Socah, Bangkalan Regency in the odd semester 2024/2025. Data obtained came from student learning results sheets and pretest and posttest questionnaire results sheets. This research uses the Problem Based Learning (PBL) model which is applied in 2 cycles. In cycle I it shows the lowest value of 15 and the highest value of 50. Furthermore, in cycle II it shows the lowest value of 75 and the highest value of 100. Classical completion in cycle I is 50% and in cycle II there is an increase of 100%. The results of this research are that through the application of Problem Based Learning (PBL) it can improve science learning outcomes in Class VIII UPTD SMP Negri 2 Socah. Based on the results of this research, researchers suggest that the problem based learning model can be used to improve student learningÂ outcomes.Keywords: Learning Outcomes; Science; Problem Based Learning